Does Regular Harvesting Increase Plant Diversity in Buffer Strips Separating Agricultural Land and Surface Waters? - Hille, Sandra; Larsen, Søren E.; Rubæk, Gitte H.; Kronvang, Brian; Baattrup-Pedersen, Annette (Frontiers in Environmental Science, 2018)
Vegetated buffer strips are often established in agricultural landscapes as an ‘edge of the field’ mitigation measure against diffuse nutrient pollution of the aquatic environment. Harvesting of the vegetation has been suggested as a possible management strategy to prevent build-up of excessive amounts of nutrients in buffer soils and, at the same time, harvesting can have a positive effect on the diversity of the vegetation. However, the response of the vegetation to harvesting likely depends on taxonomic and functional characteristics. In the present study, we explored effects of harvesting frequency (by comparing harvesting once, twice and four times per year to an unharvested control) on the taxonomic and functional trait composition of four different types of plant communities in buffer strips in Denmark. We found that one to two harvests per year mediated an increase in the diversity of the vegetation in low diversity buffer strips dominated by tall and productive herbs (tall herb fringe), whereas the diversity remained unchanged in more diverse buffer strips dominated by grasses as well as in buffer strips with rich fen and wet meadow species. We also found that harvesting changed the compositional patterns in the tall herb fringe community, with an increasing abundance of grasses and a declining abundance of tall herb species, in particular at a high harvesting frequency. Concomitant with these taxonomic changes, we observed changes in the trait composition of the community. The abundance of tall species declined in the tall herb fringe and in the tall grass community. Similarly, the abundance of productive species (as indicated by high Ellenberg N and Ellenberg R values) declined in the tall herb fringe (in areas harvested four times per year). We conclude that low frequency harvesting is a promising management strategy to increase plant diversity in buffer strips with an initially low diversity and high productivity and that harvesting over time can mediate a shift in compositional patterns towards less productive species.